PENGARUH TERAPI MUROTAL AR RAHMAAN TERHADAP PENURUNAN INTENSITAS NYERI PADA PASIEN POST OPERASI CAESAR DI RSUD Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Annisa Priliana; Atun Raudotul Ma’rifah; Noor Yunida Triana (Viva Medika, 2014)
Pain is a sensory experience and an unpleasant emotion due to actual orpotential tissue damage. Pain in post-caesarian surgery incision area will causediscomfortness. one of non-pharmacologic to reduce the pain is a hearing disractionby murotal surah Ar Rahmaan. The objective from this research is to knowing an effect of murotal ArRahmaan therapy to reduce the intensity of pain of a post-caesarian surgery patientat RSUD Prof. Dr. Margono Soekarjo Purwokerto This research use an pre-experimental pathway and use an pretest-posttestdesign. The data acquired by using a 0 - 10 numeric pain scale. Sample in thisexperiment is a patient that had been over a caesarian surgery procedure. Thesampling technique used in this research is an accidental sampling, but the amount ofsampel is limited to 30 samples. The statistical test in this research is a paired t test. The research shows a reduction of a pain mean level, which is shows 6,53 apain mean level before therapy given and 3,63 after the therapy Murotal Ar Rahmaanis given. P score 0,000 (0,05) and count t 11,164 (> t table). In order of that, Ho getrejected and Ha accepted. Based of the description above we can conclude there's a positive effect ofMurotal Ar Rahmaan therapy to reduce pain intensity of post-caesarian surgery inRSUD Prof. Dr. Margono Purwokerto, so that this therpy can be used ascomplimentary therapy to reduce pain intensity. Keyword: pain, post-caesarian surgery, Murotal Ar Rahmaan